2020
DOI: 10.3389/fnut.2020.00026
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Biofortified Rice Varieties: Challenges, Possibilities, and Progress in India

Abstract: Zinc malnutrition is a major issue in developing countries where polished rice is a staple food. With the existing significant genetic variability for high zinc in polished rice, the development of biofortified rice varieties was targeted in India with support from HarvestPlus,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 28 publications
(32 reference statements)
3
44
0
Order By: Relevance
“…The loss of grain Zn during polishing is due to the loss of aleurone layer, which was reported to be significant for mineral content in rice (Sellappan et al, 2009). Previous studies reported a loss to the tune of 5 to 30% of grain Zn during the polishing in germplasm and mapping populations (Lee et al, 2008;Rao et al, 2020). Two significant conclusions from stepwise regression analysis in the present study were the determination of threshold of grain Zn in brown rice viz., for fulfilling international threshold value of rice grain Zn content (28 ppm), the developers may need to target ≥ 38.5 ppm increase in ZBR.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…The loss of grain Zn during polishing is due to the loss of aleurone layer, which was reported to be significant for mineral content in rice (Sellappan et al, 2009). Previous studies reported a loss to the tune of 5 to 30% of grain Zn during the polishing in germplasm and mapping populations (Lee et al, 2008;Rao et al, 2020). Two significant conclusions from stepwise regression analysis in the present study were the determination of threshold of grain Zn in brown rice viz., for fulfilling international threshold value of rice grain Zn content (28 ppm), the developers may need to target ≥ 38.5 ppm increase in ZBR.…”
Section: Discussionsupporting
confidence: 51%
“…Identification of environmentally stable donor lines for high grain Zn would contribute and accelerate the development of biofortified Zn rice varieties. Several landraces have been identified with grain Zn up to 58.4 ppm in brown rice (Gregorio et al, 2000;Norton et al, 2014;Tan et al, 2020) and up to 40.9 ppm in polished rice across world since 2000 (Lee et al, 2008;Bollinedi et al, 2020;Rao et al, 2020). But reports on validation of the identified landraces with high grain Zn for their stability across environments and systematic deployment of identified landraces as donors in breeding of Zn biofortified rice varieties are limited.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations